BEYOND NORMATIVE INSTRUCTION: THE INTERNALIZATION OF SATLOGI SANTRI IN AN INDONESIAN ISLAMIC BOARDING SCHOOL - Imam Bukhori (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study explores how Satlogi Santri serves as a framework for local cultural values, shaping students' character and moral awareness at the Zainul Hasan Genggong Islamic Boarding School. The research aims to provide a contextual understanding of value education, beyond normative teaching, by examining it as a lived cultural process. A qualitative approach with an ethnographic educational design was used. Data were collected through in-depth interviews with students, senior students, and pesantren administrators, as well as participant observation and document analysis. Thematic analysis was conducted to examine the relationship among the Santri Satlogi value framework, the process of value meaning, and the embodiment of character in students’ daily practices. The findings reveal that Satlogi Santri is not explicitly taught but internalized through shared life experiences, social relationships, and repetitive habits. The values are concretely recognized through the Nine Main Virtues of Santri, which serve as indicators of moral maturity within the pesantren community. This study confirms that character development in pesantren occurs as a sustainable cultural process. It contributes to the development of value education studies grounded in local cultural wisdom and pesantren traditions, emphasizing the importance of lived experience in moral education.